Validity and Legal Consequences of Granting Building Use Rights to the Komanditer/Comanditaire Venootshap Guild (CV) - Muhamad Mahdifa Lazuardi; Siti Hajati Hoesin (IHSA Institute, 2022)
The granting of Building Use Rights (hereinafter referred to as HGB) cannot be given to limited partnerships. This is because the Limited Partnership is a business entity, while what can be granted HGB is a legal entity. HGB is the right to construct or own a building on land that is not one's own for a limited period of time. In Indonesia, this HGB is regulated in the Basic Agrarian Law (hereinafter referred to as UUPA) and those who can own this HGB are Indonesian Citizens (WNI) and legal entities established and domiciled in Indonesia as described in Article 36 paragraph (1 ) UUPA. In practice, there is a policy that allows these Limited Partnerships to own HGB as contained in Circular Letter Number 2/SE-HT.02.01/VI/2019 issued by the Minister of Agrarian Affairs and Spatial Planning regarding the Granting of HGB to Limited Partnerships. This Circular Letter aims to increase investment and encourage economic growth in all regions of Indonesia by granting HGB to Limited Partnerships. This research focuses on discussing the suitability and legal consequences of granting HGB to limited partnerships based on Circular Letter Number 2/SE-HT.02.01/VI/2019. This study uses a normative juridical method with a statutory approach and an analytical approach. This research will explain the granting of HGB based on the UUPA and government regulations, the status of limited partnerships in Indonesia, and the legal consequences of enforcing Circular Letter Number 2/SE-HT.02.01/VI/2019 on obtaining HGB for limited partnerships.